Interpretasi Pragmatis Analogis Metafora Bahasa Bali - Nengah Arnawa (Jurnal Kajian Bali (Journal of Bali Studies), 2016)
The research focused on semantic classification of Balinese metaphor. The research was intended to identify interpreting patterns of metaphor implicature. Thus, the theory underlying the research was semantic and pragmatic theories. The research design was ethnography of communication. Research data was collected from the use of metaphor of written and spoken text or domain. The data was analyzed with qualitative method. Result of analysis indicated that semantically, Balinese metaphor was dominated by concrete-abstract type of metaphor with quiet high tension. Metaphorical implicature was designed through two analogical patterns, they are logical and declarative analogy. The use of metaphor was based on cooperation and politeness principle.